Zebularine treatment is associated with deletion of FT‐B1 leading to an increase in spikelet number in bread wheat. (6th April 2018) - Finnegan, E. Jean; Ford, Brett; Wallace, Xiaomei; Pettolino, Filomena; Griffin, Patrick T.; Schmitz, Robert J.; Zhang, Peng; Barrero, Jose M.; Hayden, Matthew J.; Boden, Scott A.; Cavanagh, Colin A.; Swain, Steve M.; et al.
Abstract: The number of rachis nodes (spikelets) on a wheat spike is a component of grain yield that correlates with flowering time. The genetic basis regulating flowering in cereals is well understood, but there are reports that flowering time can be modified at a high frequency by selective breeding, suggesting that it may be regulated by both epigenetic and genetic mechanisms. We investigated the role of DNA methylation in regulating spikelet number and flowering time by treating a semi‐spring wheat with the demethylating agent, Zebularine. Three lines with a heritable increase in spikelet number were identified. The molecular basis for increased spikelet number was not determined in 2 lines, but the phenotype showed non‐Mendelian inheritance, suggesting that it could have an epigenetic basis. In the remaining line, the increased spikelet phenotype behaved as a Mendelian recessive trait and late flowering was associated with a deletion encompassing the floral promoter, FT ‐ B1. Deletion of FT‐B1 delayed the transition to reproductive growth, extended the duration of spike development, and increased spikelet number under different temperature regimes and photoperiod. Transiently disrupting DNA methylation can generate novel flowering behaviour in wheat, but these changes may not be sufficiently stable for use in breeding programs. Abstract : We investigated whether the demethylating agent Zebularine could be used as a tool to generate novel phenotypes for wheat breeding programs. Zebularine treatment delayed flowering and increased spikelet number in three plants of a semi‐spring wheat variety. The increased spikelet phenotype in two of these lines showed non‐Mendelian inheritance suggesting that it could be associated with a transient loss of DNA methylation, whereas in the third line, this phenotype was conditioned by a stably inherited recessive trait associated with deletion of FT ‐ B1, a major gene controlling flowering time in wheat. Loss of FT ‐ B1 resulted in increased spikelet number under all environmental conditions tested; the robust nature of this phenotype suggests that this deletion could be a valuable resource for breeding wheat with increased yield.